THE USE OF ADVERTISEMENT IN SOCIAL MEDIA TO ENRICH STUDENTS’ VOCABULARY - Arli Adinda; Hanafi Wibowo; Enci Zarkasih (Lingua, 2021)
This study aims to at improving the vocabulary mastery in students' vocabulary by using advertisement media for grade 9 at SMPN 168 Jakarta. This research is a Classroom Action Research conducted, each cycle consists of 4 stages, namely: planning, action, observation and reflection with the research process (1) learning by using advertising media (2) planning the form of action in cycle 2 based on the results of cycle 1 reflection. research indicators show an increase in student learning outcomes. The research subjects were grade 9 students at SMPN 168 Jakarta in the odd semester 2021/2022, totaling 18 students. The results showed that in the cycle. The results showed that in the first cycle only 11 students (61.2%) achieved the KKM score (75), while 7 students (38.8%) were below the KKM score. The second cycle showed that only 2 people (11.4%) did not reach the KKM score. Meanwhile, 16 students (88.6%) whose scores exceed the KKM. The description of learning outcomes through advertising media for grade 9 students based on the results of the second cycle test, namely in the complete category reaching 88.6 percent and only a few students having learning outcomes through advertising media, namely 11.4 percent, in the first cycle students who completed only 61.2 percent and not completed as much as 38.8 percent. This illustrates that learning with the learning model with advertising media has been going well and can support increasing vocabulary with advertising media on social media. Therefore, it is recommended that teachers in teaching subject matter should prioritize the use of cooperative learning models using advertising media on social media.